Productivity improvements using lean practices at japanese electrical and electronics manufacturing - Afif Aimaduddin Parnon, 1986- author; Muhamad Zameri Mat Saman; Fakulti Kejuruteraan Mekanikal (2015)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2015